Identification of an AGO (Argonaute) protein as a prey of TER94/VCP. Issue 1 (2nd January 2020) - Kobayashi, Hotaka; Tomari, Yukihide
ABSTRACT: VCP (valosin containing protein) recognizes a wide variety of substrates and mediates their degradation via the ubiquitin-proteasome system and macroautophagy/autophagy. The substrate repertoire of VCP, however, is not fully understood. In our recent study, we found that Drosophila TER94/VCP mediates autophagic degradation of an Argonaute subfamily protein (AGO1), which binds microRNAs (miRNAs) and silences the expression of thousands of target genes. In the absence of TER94/VCP, miRNA-mediated gene silencing is globally impaired. Our findings reveal an unexpected connection between VCP and AGO, which may dramatically expand the biological significance of VCP.